Analisa Modul Ajar IPAS & Pelaksanaan Pembelajaran di SD Negeri 060877 Medan Perjuangan - Ratno, Suyit; Putri Silalahi, Rachel Dewi; Binjori, Clara Sriyusniar; Badzlina, Jihan; Warni, Dwi Sulistianing; Az Zahra, Nazwa; Lamtama Tampubolon, Yosep Tio (UNIVERSITAS SERAMBI MEKKAH, 2025)
The purpose of this research is to evaluate the teaching module for Natural and Social Sciences (IPAS) at SD Negeri 060877 Medan Perjuangan and to measure its effectiveness in the teaching and learning process. This is important because the curriculum must continuously be updated in accordance with advancements in science and technology, as well as the students' need for higher-order thinking skills (HOTS) in current education. Using a descriptive qualitative approach, information was obtained through observations, interviews with teachers, and analysis of the teaching module documents. The results indicate that the IPAS teaching module incorporates elements of Bloom's Taxonomy, with some aspects reflecting lower-order thinking skills (LOTS) and higher-order thinking skills (HOTS). Although the module includes HOTS elements, there is still a need to add more challenging activities to foster creativity and innovation among students. This research recommends the development of teaching modules to enhance the quality of learning in the fourth grade.